Ecology and distribution of mosquito larvae in the inland habitat of south Sulawesi, Indonesia - Awaluddin,; Sugiarto,; M Ikhsan, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The ecology and distribution of mosquito larvae have a significant effect on mosquito populations and in arbovirus transmission. There is no information on the ecology and distribution of mosquito larvae in the inland area of South Sulawesi, Indonesia. This study aimed to examine distribution and ecological of mosquito larvae that affect the survival of arbovirus vectors in the inland area of South Sulawesi. Larvae were obtained in eight locations of the South Sulawesi region. The collected samples were examined in the Entomology Laboratory, Faculty of Medicine, Hasanuddin University, South Sulawesi, Indonesia. Larvae were counted, separated by genus and identified to the species level. The physical parameters of the water in the breeding sites (pH, temperature and salinity) and the ambient relative humidity were recorded. Data were analyzed using IBM SPSS version 24 and the spatial distribution of larvae was mapped using ArcGIS version 10.5. Results showed that there were 3,803 larvae consisting of Ae. aegypti, Ae. albopictus, Cx. quinquefasciatus, Cx. vishnui, Cx. tritaenorynchus, Cx. gelidus, and An. vagus. The physical parameters of the water habitat for mosquito larvae range from a temperature of 24.5°C-34.2°C, water pH 6.3-7.5, humidity 67.8- 89.0, and salinity 0 ppt. We found that mosquito larvae abundant had a significant relationship (P=0.00) with pH, salinity, temperature, and humidity. Results suggest that the abundance of arbovirus vectors in the inland of South Sulawesi can be controlled by vector control programs.